FAKTOR-FAKTOR PENDORONG KEBERHASILAN PEMERINTAH KABUPATEN SIAK DALAM PENANGGULANGAI KEMISKINAN DI KECAMATAN MEMPURA KABUPATEN SIAK (TAHUN 2011-2015) - Setiowati, Endang; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research is conducted by Siak District Government which succeed especially in Mempura sub-district with existing programs so that it can reduce the number of poor people of Siak Regency and increase people’s welfare. According to the Regional Regulation of Siak Regency Year 2012 poverty is a socio-economic condition of a person or group of people who are not fulfilled their basic rights to maintain and develop a life of dignity. As for formulation of the problem in this research is what factors that become the driving force of the succees of the Siak Regency government in poverty reduction in sub-district Mempura in Siak Sri Indrapura.This research type using qualitative approach with descriptive method. Data collected by the writer use interview and documentation technique. Data used is primary data obtained from informant research and then supported from various government institutions related to this research.Research shows that in tackling this poverty Siak Sri Indrapura Regecy Government has issued a policy related to poverty namely the Regional Regulation (Perda) No. 10 of 2012 on poverty reduction in Siak Regecy. These succees factors in the form of Government programs according to the local regulation. Resources Human (SDM) and the Regional Poverty Reduction Coordination Team.Keywords: Succees Factors. Poverty, Local Regulation (Perda)